2021
DOI: 10.9734/jpri/2021/v33i26b31484
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, Anti-Mycobacterial Evaluation and In-Silico Molecular Docking of Novel Isoxazole Clubbed Pyrimidine Derivatives

Abstract: In the present research, we tend to ready a series of novel pyrimidine-linked isoxazole derivatives (11-20). The molecular structure and the elemental composition of these compounds were confirmed by spectroscopic studies and elemental analysis. MABA (Microplate alamar Blue Assay) assay was employed for assessing the antitubercular activity against the Mycobacterium tuberculosis H37Rv strain. Among the ten synthesized compounds, 18 and 20 showed excellent anti-tubercular activity than the reference (MIC-3.125 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…anti-cancer and anti-tumor [12], anti-inflammatory [13], anti-convulsant [14], anti-mycobacterial [15], antiproliferative [16], anti-viral [17], anti-oxidant [18], antitubercular [19], etc. It also has been observed that isoxazole-containing scaffold also possesses good herbicidal potency proving their utilization in the agricultural sector too [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…anti-cancer and anti-tumor [12], anti-inflammatory [13], anti-convulsant [14], anti-mycobacterial [15], antiproliferative [16], anti-viral [17], anti-oxidant [18], antitubercular [19], etc. It also has been observed that isoxazole-containing scaffold also possesses good herbicidal potency proving their utilization in the agricultural sector too [20].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have reported the synthesis of varied derivatives consisting of isoxazole rings in their structure by various routes [8]. Isoxazole and their derivatives show different biological actions such as anti‐bacterial [9], analgesic [10], anti‐fungal [11], anti‐cancer and anti‐tumor [12], anti‐inflammatory [13], anti‐convulsant [14], anti‐mycobacterial [15], anti‐proliferative [16], anti‐viral [17], anti‐oxidant [18], anti‐tubercular [19], etc. It also has been observed that isoxazole‐containing scaffold also possesses good herbicidal potency proving their utilization in the agricultural sector too [20].…”
Section: Introductionmentioning
confidence: 99%
“…Among them isoxazole and dihydropyrazole were of special interest to medicinal chemists, owing to their useful biological actions. Both these rings are not only the part of many drug molecules but their derivatives were reported with significant activities including antitubercular [2][3][4][5][6][7][8][9], antioxidant [10][11], anticancer [12,13], antibacterial [14,15], antifungal [16,17]. Hence, combining these two rings into a single molecule has a greater propensity of improving the activity of new analogues.…”
Section: Introductionmentioning
confidence: 99%